KONSTRUKSI METAFORIS IDENTITAS BUDAYA DALAM PERIBAHASA INDONESIA DAN IMPLIKASINYA BAGI PENGAJARAN BIPA - Balazs Huszka; Robita Ika Annisa; Indah Aini; Rabi’atul Adawiyyah binti Haji Hassan; Nasution, Jamaluddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian proverbs represent a form of cultural heritage that embodies societal values, norms, and worldviews. The metaphorical frameworks of these proverbs describe how Indonesians perceive and understand reality. However, the usage of proverbs in teaching Indonesian for Foreign Speakers (BIPA) is still limited. This article examines the metaphorical construction of cultural identity embedded in Indonesian proverbs and investigates their relevance for BIPA instruction, particularly at the intermediate to advanced levels, in fostering cultural literacy and intercultural competence among foreign learners. This study employs a thematic analysis approach to Indonesian proverbs by identifying recurring metaphorical patterns. Categorization is used to better understand the relationship between proverbs and broader Indonesian cultural themes. The research identifies seven key metaphorical domains: (1) family and kinship, (2) nature and the environment, (3) social harmony and collectivity, (4) caution and wisdom, (5) human emotions and interpersonal connections, (6) knowledge and experience, and (7) fate and human limitations. These domains show how abstract cultural values like morality, responsibility, and resilience are understood using concrete and familiar cultural images. Integrating proverbs into the BIPA curriculum can enhance learners’ linguistic competence while deepening their understanding of Indonesian cultural identity. With their clear metaphorical foundations, proverbs can serve as effective pedagogical instruments for linking language, culture, and intercultural understanding in Indonesian language education.